Molecular Epidemiology of Tuberculosis in British Columbia, Canada: A 10-Year Retrospective Study. (21st October 2017) - Guthrie, Jennifer L; Kong, Clare; Roth, David; Jorgensen, Danielle; Rodrigues, Mabel; Hoang, Linda; Tang, Patrick; Cook, Victoria; Johnston, James; Gardy, Jennifer L
Abstract : This 10-year retrospective study describes tuberculosis molecular epidemiology in a low-incidence setting. Approximately one-third of cases likely result from local transmission, largely – but not entirely – amongst the Canadian-born. Disease site and risk factors for clustering vary with lineage and birthplace. Abstract: Background: Understanding regional molecular epidemiology allows for the development of more efficient tuberculosis prevention strategies in low-incidence settings. Methods: We analyzed 24-locus mycobacterial interspersed repetitive-unit–variable-number tandem repeat (MIRU-VNTR) genotyping for 2290 Mycobacterium tuberculosis clinical isolates collected in the province of British Columbia (BC), Canada, in 2005–2014. Laboratory data for each isolate were linked to case-level clinical and demographic data. These data were used to describe the molecular epidemiology of tuberculosis across the province. Results: We detected >1500 distinct genotypes across the 4 major M. tuberculosis lineages, reflecting BC's diverse population. Disease site and clustering rates varied across lineages, and MIRU-VNTR was used to group the 2290 isolates into 189 clusters (2–70 isolates per cluster), with an overall clustering rate of 42.4% and an estimated local transmission rate of 34.1%. Risk factors for clustering varied between Canadian-born and foreign-born individuals; the former had increased odds (odds ratio, 7.8; 95% confidence interval [CI], 6.2–9.6) of belonging to a genotypic cluster, although nearly one-quarter of clusters included both Canadian- and foreign-born persons. Large clusters (≥10 cases) occurred more frequently within the M. tuberculosis Euro-American lineage, and individual-level risk factors associated with belonging to a large cluster included being Canadian born (adjusted odds ratio, 3.3; 95% CI, 2.3–4.8), residing in a rural area (2.3; 1.2–4.5), and illicit drug use (2.0; 1.2–3.4). Conclusions: Although tuberculosis in BC largely arises through reactivation of latent tuberculosis in foreign-born persons, locally transmitted infections occur in discrete populations with distinct disease and risk factor profiles, representing groups for targeted interventions.